Rozwijanie zasobowej teorii przedsiębiorstwa jako bazy nowoczesnych koncepcji zarządzania - Nogalski, Bogdan; Falencikowski, Tadeusz (Developing the Resource-Based Theory of the Firm as a Base for Modern Managerial Concepts, 2006)
The content of the article arises from a thesis that it is not possible to understand an enterprise and influence its behavior without understanding most of all (and together with the processes occurring outside the company) the processes occurring inside it, and without referring to the theory of resources owned by an enterprise. Treating a company as a "black box" requires the construction of many rigorous assumptions which make it virtually impossible to involve the category of resources in the considerations over the functioning of the enterprise. These premises led the authors to an attempt lo shed light on the resource-based theory of the firm (RBTF). Such an aim allows an assumption of the following research hypothesis: it is possible to develop the resource-based theory of the firm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 96-105